A tomato chloroplast-targeted DnaJ protein protects Rubisco activity under heat stress - Wang, Guodong (Journal of experimental botany, 2015)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.